2021
DOI: 10.1111/jfpp.15754
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different solvents for extraction of oils from by‐products of shrimps Penaeus vannamei and Procambarus clarkia

Abstract: The effects of different extraction solvents on the extraction yield and chemical composition of oils from by-products of marine shrimp Penaeus vannamei (Pv) and freshwater shrimp Procambarus clarkia (Pc) were investigated. Our results indicated that the ethanol and n-hexane mixture (4:1, v/v) was suitable solvent for simultaneous extraction of phospholipid and nonpolar lipids. By contrast, the ethanol and n-hexane mixture (4:1, v/v) and single ethanol were suitable solvents for the extraction of polyunsaturat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 38 publications
2
8
0
Order By: Relevance
“…High extraction yield of hydro-alcohol solvents especially (20:80) hydro-ethanol can be attributed to their capability to dissolve polar along with non-polar molecules [30]. Indeed, the polarity of ethanol system is more consistent for extraction of polar components like, phospholipids, polysaccharides and lipoproteins, which may be the most dominant components of the O. stricta fruit material additionally to flavonoid and betacyanin glycosides like isorhamnetein-3-O-rutinoside, betanin, isobetanin and betanidin [5,[31][32][33]. On the other side, acetone or its combinations with water can be considered as common extractant for tannins and proanthocyanidins [7,34,35].…”
Section: Extraction Yieldmentioning
confidence: 99%
“…High extraction yield of hydro-alcohol solvents especially (20:80) hydro-ethanol can be attributed to their capability to dissolve polar along with non-polar molecules [30]. Indeed, the polarity of ethanol system is more consistent for extraction of polar components like, phospholipids, polysaccharides and lipoproteins, which may be the most dominant components of the O. stricta fruit material additionally to flavonoid and betacyanin glycosides like isorhamnetein-3-O-rutinoside, betanin, isobetanin and betanidin [5,[31][32][33]. On the other side, acetone or its combinations with water can be considered as common extractant for tannins and proanthocyanidins [7,34,35].…”
Section: Extraction Yieldmentioning
confidence: 99%
“…Many studies have also shown that marine animals were rich in PLs, and most of the female gonads contained more PLs than the male ones. [ 26–28 ] For example, Hayashi [ 29 ] reported that the majority of lipids in the gonads of arrow squid ( Loligo bleekeri ) were PLs, which accounted for 83.3% and 80.3% of the total lipids in female and male gonads, respectively. Besides, Palacios et al.…”
Section: Resultsmentioning
confidence: 99%
“…Espinosa-Pardo et al realized that ethanol compared to hexane, had a better ability to increase the extraction yield of corn germ oil due to the extraction of other polar compounds from the lipid matrix [ 40 ]. Accordingly, higher EE of n -hexane/ethanol may be contributed to the separation of phospholipids by the polar phase (ethanol) and more nonpolar lipids like triglycerides by the non-polar phase ( n -hexane) [ 38 , 41 ]. Recently, a combination of these two solvents (hexane/ethanol; 1:4 v / v ) has resulted in the highest efficiency in extracting oil from shrimp by-products [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, higher EE of n -hexane/ethanol may be contributed to the separation of phospholipids by the polar phase (ethanol) and more nonpolar lipids like triglycerides by the non-polar phase ( n -hexane) [ 38 , 41 ]. Recently, a combination of these two solvents (hexane/ethanol; 1:4 v / v ) has resulted in the highest efficiency in extracting oil from shrimp by-products [ 41 ]. The high ability of polar solvents to increase EE of LMOs explains that the alcoholic mixture contained more polar lipids such as mono-glycerides (MAG), di-glycerides (DAG), phospholipids, and lipoproteins) than n -hexane or its combination with each of the alcohols.…”
Section: Resultsmentioning
confidence: 99%